Responsible Business Conduct in the European Union’s Investment Policy - Janina Witkowska (Comparative Economic Research)
This paper aims to characterize the role of responsible business conduct (RBC)/corporate social responsibility (CSR) within the European Union’s (EU) common investment policy. It explores how the EU uses CSR/RBC to promote sustainable development in the context of foreign direct investment (FDI). The main research objectives include an assessment of the potential impact of the provisions on CSR/RBC included in the EU’s international trade/investment agreements on achieving the sustainable goals in host and home countries of FDI, methods of implementing these provisions in international relations, and the future role of the World Trade Organization’s (WTO) Investment Facilitation Framework for Development (IFD) Agreement in reshaping the EU’s investment policy. The study employs qualitative methods, supported by the examination of examples of the EU’s new generation of international trade and economic partnership agreements (Korea, Canada, and Japan). The EU treats RBC/CSR as a crucial tool for achieving the UN Agenda 2030’s sustainable development goals. Responsible business behavior is promoted and supported by the instruments of the EU’s trade and investment policies. Since RBC/CSR is voluntary, agreements are enforced through soft measures and actions. The only strong instrument, i.e., trade sanctions, is treated as the last resort and has not been used so far. The newly negotiated WTO Investment Facilitation for Development (IFD) Agreement is expected to enhance the re‑orientation of the EU’s policy towards facilitating foreign investment in relations with developing countries. The paper’s main contribution lies in its examination of the EU’s approach towards CSR/RBC in its international trade/investment agreements. It also analyses the problems associated with implementing RBC/CSR provisions within these agreements.